Notes on west Palaearctic species of the genus Trigonurus Mulsant, 1847 (Coleoptera: Staphylinidae: Trigonurinae) - Hlaváč, Peter; Kocian, Matúš (Zootaxa, 2016)
The subfamily Trigonurinae Reiche, 1866 is a monogeneric subfamily of the large family Staphylinidae with an Holarctic distribution. The genus was the subject of a revision (Blackwelder, 1941). Seven species are known from northern America (Blackwelder, 1941; Herman, 2001), two species from the western Palaearctic and two, recently described species from China (Schülke & Smetana, 2015; Kishimoto, 2000; Schülke, 2006).